An Overview of the BALSAC Population Database. Past Developments, Current State and Future Prospects - Hélène Vézina; Jean-Sébastien Bournival (Historical Life Course Studies)
The BALSAC database, developed since 1971, contains data on the Quebec population from the beginnings of European settlement in the 17th century to the contemporary period. Today, BALSAC is a major research infrastructure used by researchers from Quebec and elsewhere, both in the social sciences and in the biomedical sciences. This paper presents the evolution and current state of the database and offers a perspective on forthcoming developments. BALSAC contains marriage certificates until 1965. Coverage is complete for Catholic records (80 to 100% of the population depending on the region and the period) and partial for the other denominations. Birth and death certificates from all Catholic parishes have been integrated for the period 1800–1849 and work in underway for 1850–1916. All the records entered in BALSAC are subject to a linkage process which, ultimately, allows the automatic reconstitution of genealogical links and family relationships. The basic principle has remained the same since the beginning, namely to match individuals based on the nominative information contained in the sources. The changes made in recent years and the resulting gains are mostly related to IT advances which now offer more flexibility and increased performance. Future perspectives rest on the diversification of the sources of population data entered or connected to the database and, as a corollary, by continuous optimization of data processing and linkage procedures. In the era of 'big data', BALSAC is gradually moving from a historical population database to a multifaceted infrastructure for interdisciplinary research on the Quebec population.